DIGITAL FINANCIAL LITERACY MAHASISWA CALON GURU VOKASI BIDANG BISNIS DAN MANAJEMEN DI PROVINSI RIAU - Baskara, Agus; Eeng Ahman; Disman (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
This research was conducted to identify the level of digital financial literacy among aspiring vocational education students in Riau Province. A critical talent in the digital age is financial literacy, particularly in the context of business and financial transactions that increasingly incorporate technology. 226 participants from a private institution in Riau Province's Accounting Education Study Program participated in this study. This study uses quantitative descriptive research methodologies to provide a thorough picture of the digital financial literacy of prospective vocational teachers. According to the study's findings, vocational teacher candidates in Riau Province have a sufficient understanding of digital financial products and services (75.18%) and experience using digital financial products and services (74.04%), but their knowledge of digital financial risks (55.79%) and expertise in managing digital financial resources (51.67%) are still lacking. Men and women who are financially literate online do differ slightly, but they nonetheless confront many of the same obstacles. As a result, the vocational teacher education curriculum must adopt a learning strategy that places a greater emphasis on digital financial hazards and practical financial management abilities.